A genetically encoded photoactivatable Rac controls the motility of living cells - Wu, Yi I.; Frey, Daniel; Lungu, Oana I.; Jaehrig, Angelika; Schlichting, Ilme; Kuhlman, Brian; Hahn, Klaus M. (Nature (London), 2009)
A light touch on proteins Many aspects of cellular function depend on when and where in the cell various protein activities are turned 'on' or 'off' at the molecular level. A new technique that uses light to manipulate the activity of a protein at precise times and places within the living cell has the potential make the study of this fundamental aspect of protein function a practical proposition. It makes use of a genetically encoded, photoactivatable derivative of Rac1, a GTPase that regulates actin cytoskeletal dynamics, which can be activated by exposure to laser light. This localized activation generates precisely localized cell protrusions and ruffling and can direct cell motility. This approach should be extensible to other proteins. The precise spatiotemporal dynamics of protein activity remain poorly understood, yet they can be critical in determining cell behaviour. A genetically encoded, photoactivatable version of the protein Rac1, a key GTPase regulating actin cytoskeletal dynamics, has now been produced; this approach enables the manipulation of the activity of Rac1 at precise times and places within a living cell, thus controlling motility. The precise spatio-temporal dynamics of protein activity are often critical in determining cell behaviour, yet for most proteins they remain poorly understood; it remains difficult to manipulate protein activity at precise times and places within living cells. Protein activity has been controlled by light, through protein derivatization with photocleavable moieties 1 or using photoreactive small-molecule ligands 2 . However, this requires use of toxic ultraviolet wavelengths, activation is irreversible, and/or cell loading is accomplished via disruption of the cell membrane (for example, through microinjection). Here we have developed a new approach to produce genetically encoded photoactivatable derivatives of Rac1, a key GTPase regulating actin cytoskeletal dynamics in metazoan cells 3 , 4 . Rac1 mutants were fused to the photoreactive LOV (light oxygen voltage) domain from phototropin 5 , 6 , sterically blocking Rac1 interactions until irradiation unwound a helix linking LOV to Rac1. Photoactivatable Rac1 (PA-Rac1) could be reversibly and repeatedly activated using 458- or 473-nm light to generate precisely localized cell protrusions and ruffling. Localized Rac activation or inactivation was sufficient to produce cell motility and control the direction of cell movement. Myosin was involved in Rac control of directionality but not in Rac-induced protrusion, whereas PAK was required for Rac-induced protrusion. PA-Rac1 was used to elucidate Rac regulation of RhoA in cell motility. Rac and Rho coordinate cytoskeletal behaviours with seconds and submicrometre precision 7 , 8 . Their mutual regulation remains controversial 9 , with data indicating that Rac inhibits and/or activates Rho 10 , 11 . Rac was shown to inhibit RhoA in mouse embryonic fibroblasts, with inhibition modulated at protrusions and ruffles. A PA-Rac crystal structure and modelling revealed LOV–Rac interactions that will facilitate extension of this photoactivation approach to other proteins.